PENGARUH PEMBERIAN KREDIT USAHA RAKYAT (KUR) TERHADAP PENDAPATAN USAHA MIKRO PADA PT. BANK SULSELBAR KANTOR PUSAT MAKASSAR - Hasyim Mochtar (P3M STIEM BONGAYA, 2019)
This study aims to determine whether the effect of granting People's Business Credit (KUR)on Micro Business revenue at PT. Bank Sulselbar Makassar Head Office. Data collection usesprimary data. The population used was obtained from the Micro Small Business data, while thesample is 38 data obtained from the research period of 1 year. The analytical method used is a simplelinear regression analysis, supplemented by a test of the classical assumptions of normality,multicollinearity, and heteroscedasticity.The results of this study are known in the correlation test (Ttest) that the significant value of tcount> ttable is 2,440> 2,028. This shows that more and morePeople's Business Credit (KUR) given to customers can be put to good use by Micro Business actorsfor venture capital besides giving People's Business Credit (KUR) proposed by customers inaccordance with their wants and business needs